Patterns and Trends of Crocodile Trade from Tanah Papua, Indonesia - Dewi Untari; Hardjanto Hardjanto; Bramasto Nugroho; Rinekso Soekmadi (Forest and Society, 2020)
Crocodylus porosus and C. novaeguineae are two protected and tradable crocodile species in Indonesia. Therefore, precautionary principles are needed in their utilization to ensure sustainability. Although the commodity from these species is traded domestically and internationally, the broader picture of its use in Indonesia is less known. The objectives of the study were to: (1) analyze the domestic trade of crocodiles, and (2) analyze the international trade of crocodiles. The analysis was conducted using data of direct utilization sourced from the wild in the form of skin and hatchlings, data on domestic transport permits, CITES export permits, and the CITES trade database. The study suggested that the harvest of crocodile hatchlings and skin do not represent the actual condition since the skin recorded were only those sent outside of the province. Determining zero harvest quotas of C. porosus did not stop species harvest for domestic trade. The dominant source of C. porosus skin export was captive breeding, while C. novaeguineaewas sourced from the wild. Ranch-sourced skin of both species for export were very low.